PENGARUH KOMPENSASI, MOTIVASI DAN KEPUASAN KERJA TERHADAP KOMITMEN PEGAWAI KELURAHAN SAWAHAN, KECAMATAN PONJONG, KABUPATEN GUNUNGKIDUL - Syaif Abdullah (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
This study aimed to examine the effect of Compensation, Motivation, and Job Satisfaction Employee Commitment Against Urban Sawahan Village, District Ponjong, Gunungkidul, Yogyakarta. Another objective of this study was to determine the effect of compensation on the commitment, motivation influence on commitment, influence job satisfaction and commitment to the simultaneous effect of compensation, motivation, job satisfaction on commitment. This study uses a quantitative approach with a survey method in which data is collected using a questionnaire. The primary data in this study were obtained from 30 Employees Sawahan Village, District Ponjong, Gunungkidul, Yogyakarta . Analytical tool in this study is multiple regression , to see the effect of compensation , motivation, and job satisfaction on commitment. The results of the analysis of multiple regersi Y = -0.020 + 0.666 X1 X2 - 0.028 X3, indicating that the compensation does not affect the commitment ( -0.020 ), positively affect motivation to commitment ( 0.666 ), and job satisfaction has no effect on commitment ( -0.028 ). Simultaneously compensation, motivation, and job satisfaction have a significant effect ( 0.003 ) on the commitment. Keywords : compensation , motivation , job satisfaction , commitment.